2021
DOI: 10.1038/s41598-021-86068-7
|View full text |Cite
|
Sign up to set email alerts
|

Long read, isoform aware sequencing of mouse nucleus accumbens after chronic cocaine treatment

Abstract: To better understand the full-length transcriptome of the nucleus accumbens (NAc)—a key brain reward region—in chronic cocaine treatment, we perform the first single molecule, long-read sequencing analysis using the Iso-seq method to detect 42,114 unique transcripts from mouse NAc polyadenylated RNA. Using GENCODE annotation as a reference, we find that over half of the Iso-seq derived transcripts are annotated, while 46% of them harbor novel splicing events in known genes; around 1% of them correspond to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These sequences can be compared to known AS annotations or can be used for de novo splicing identification. While this technology has not been applied extensively to brain tissue, one recent report ( Estill et al, 2021 ) looked at isoform usage in the nucleus accumbens (NAc) of mice and found that 46% of the detected transcripts harbored novel splicing events not detected by previous RNA-seq experiments, indicating that we are missing significant amounts of AS events using normal RNA-seq for isoform detection and that long read Iso-seq technologies will be necessary for complete isoform detection.…”
Section: Bioinformatic Approaches To Brain Transcriptomic Studiesmentioning
confidence: 99%
“…These sequences can be compared to known AS annotations or can be used for de novo splicing identification. While this technology has not been applied extensively to brain tissue, one recent report ( Estill et al, 2021 ) looked at isoform usage in the nucleus accumbens (NAc) of mice and found that 46% of the detected transcripts harbored novel splicing events not detected by previous RNA-seq experiments, indicating that we are missing significant amounts of AS events using normal RNA-seq for isoform detection and that long read Iso-seq technologies will be necessary for complete isoform detection.…”
Section: Bioinformatic Approaches To Brain Transcriptomic Studiesmentioning
confidence: 99%
“…Estill et al . analysed the transcriptome of the nucleus accumbens in the brains of mice treated with cocaine, and found many novel transcripts and splicing sites, revealing information useful in our understanding of addiction and reward 6 .…”
mentioning
confidence: 99%
“…In a paper included in this Collection, Williams et www.nature.com/scientificreports/ splicing of CAMK2G in two mouse models and revealed the relationship between CAMK2G and hypoxia inducible factor 1 in the pathogenesis of heart diseases 5 . Estill et al analysed the transcriptome of the nucleus accumbens in the brains of mice treated with cocaine, and found many novel transcripts and splicing sites, revealing information useful in our understanding of addiction and reward 6 . Although every single cell in an organism carries the same genome content, different cell types can use different portions of the same genome by expressing different subsets of all possible genes.…”
mentioning
confidence: 99%